2016
DOI: 10.1242/jeb.130765
|View full text |Cite
|
Sign up to set email alerts
|

A flavanoid component of chocolate quickly reverses an imposed memory deficit

Abstract: The ability to remember is influenced by environmental and lifestyle factors, such as stress and diet. A flavanol contained in chocolate, epicatechin (Epi), has been shown to enhance long-term memory (LTM) formation in Lymnaea. Combining two stressors (low-calcium pond water and crowding) blocks learning and all forms of memory; that is, this combination of environmentally relevant stressors creates a memory-unfriendly state. We tested the hypothesis that Epi will immediately reverse the memory-unfriendly stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
1
18
0
2
Order By: Relevance
“…(−)-Epicatechin (EC) is a brain-permeable, natural flavanol compound extracted from green tea and cocoa [20, 21] that exerts protective effects on cognition [22], vascular function [23], and ischemic stroke injury [24] in animals and humans. EC has the ability to cross the blood-brain barrier (BBB) both in vivo [25] and in vitro [26].…”
Section: Introductionmentioning
confidence: 99%
“…(−)-Epicatechin (EC) is a brain-permeable, natural flavanol compound extracted from green tea and cocoa [20, 21] that exerts protective effects on cognition [22], vascular function [23], and ischemic stroke injury [24] in animals and humans. EC has the ability to cross the blood-brain barrier (BBB) both in vivo [25] and in vitro [26].…”
Section: Introductionmentioning
confidence: 99%
“…Using this procedure GT was shown to enhance or to reverse a blockade of LTM formation [1315]. Here we found (Figure 2) that training in the 1:14 BT blocked LTM formation.…”
mentioning
confidence: 57%
“…Previously we showed that a natural food substance, Epi, that is present in a number of foods was able to enhance LTM formation if the snail was trained in Epi-PW or was placed in Epi-PW during the consolidation period following training in PW [1315,19]. More recently we showed that LTM enhancement also occurs when snails are trained in food substances (e.g.…”
mentioning
confidence: 99%
“…W pierwszym flawonoidy oddziałują z kaskadami przekazywania sygnałów neuronalnych (głównie z kaskadami sygnałowymi kinaz białkowych i lipidowych), w drugim indukują obwodowy i mózgowy przepływ krwi w sposób prowadzący do angiogenezy i wzrostu nowych komórek nerwowych w hipokampie. Regularne spożywanie flawonoidów może zatem potencjalnie zmniejszyć neurodegradację skutkującą różnymi zaburzeniami neurologicznymi, nie tylko zmniejszyć częstość występowania upośledzenia funkcji poznawczych, ale wręcz je wzmocnić [70,71,72]. W krajach o wysokim poziomie spożycia czekolady w przeliczeniu na jednego mieszkańca odnotowano największą liczbę laureatów Nagrody Nobla [73].…”
Section: Demencja I Umiejętności Poznawczeunclassified
“…Według różnych badań epikatechina jest związkiem występującym w największych ilościach w ziarnach kakaowych, stanowi ona około 35% całkowitej zawartości fenoli [78]. Wykazano, że epikatechina nie tylko odwraca zaburzenia poznawcze, ale wzmacnia też tworzenie pamięci długotrwałej [71]. Obecność epikatechiny w kakao i czekoladzie związana jest z ich korzystnym oddziaływaniem na śródbłonek naczyniowy, co wynika z jej wpływu na regulację wytwarzania tlenku azotu.…”
Section: Demencja I Umiejętności Poznawczeunclassified